Role of the Summer Monsoon Variability in the Collapse of the Ming Dynasty: Evidences From Speleothem Records. Issue 11 (6th June 2021) - Zhao, Jingyao; Cheng, Hai; Yang, Yan; Liu, Wen; Zhang, Haiwei; Li, Xianglei; Li, Hanying; Ait‐Brahim, Yassine; Pérez‐Mejías, Carlos; Qu, Xiaoli
Abstract: Climatic changes have played an important role in societal reorganizations. Particularly, the late 16th and early 17th century coincided with severely cold condition, extremely weak summer monsoon and widespread population decline in China. Here we present new speleothem oxygen isotope records across North and South China, which in concert with historical documents, allow us to characterize the "Late Ming Weak Monsoon Periods" (LMWMP) at an unprecedented annual temporal resolution. Our analysis suggests that as a weak summer monsoon event not seen for nearly 500 years in China, the LMWMP spatiotemporally coincided with the late Ming Dynasty peasant uprising (1627–1658 CE), and thus the transition from Ming to Qing Dynasty. This suggests a plausible role of climate change in shaping the important chapters of the Chinese history. In addition, both speleothem and historical documents reveal that the LMWMP appears to be a north to south time‐transgressive event on decadal‐timescale. Plain Language Summary: This study presents two new speleothem paleoclimate records across northern and southern China, which in concert with the historical documents, allow us to characterize the Late Ming Weak Monsoon Periods (LMWMP) (1580–1660 CE). The records offer that the unprecedented, long‐lasting aridity/weakening monsoon period was spatiotemporally synchronized with the late Ming peasantry uprising (1627–1658 CE) and the fall of the Ming Dynasty. The comparisons with many regional paleoclimate records show that the severest drought during the LMWMP was time‐transgressive on decadal‐timescale: from northern China to the Jiang‐Huai region. Mechanistically, solar activity may provide a centennial scale background of precipitation decreases for LMWMP. Key Points: The Late Ming Weak Monsoon Period (LMWMP) spatiotemporally coincided with the late Ming Dynasty peasant uprising, and thus the transition from Ming to Qing Dynasty. Both speleothem and historical documents reveal that the LMWMP appears to be a north to south time‐transgressive event on decadal‐timescale. It suggests a plausible role of climate change in shaping the important chapters of the Chinese history.